2016
DOI: 10.1093/brain/aww016
|View full text |Cite
|
Sign up to set email alerts
|

Eliminating microglia in Alzheimer’s mice prevents neuronal loss without modulating amyloid-β pathology

Abstract: In addition to amyloid-β plaque and tau neurofibrillary tangle deposition, neuroinflammation is considered a key feature of Alzheimer's disease pathology. Inflammation in Alzheimer's disease is characterized by the presence of reactive astrocytes and activated microglia surrounding amyloid plaques, implicating their role in disease pathogenesis. Microglia in the healthy adult mouse depend on colony-stimulating factor 1 receptor (CSF1R) signalling for survival, and pharmacological inhibition of this receptor re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

43
529
7
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 561 publications
(599 citation statements)
references
References 89 publications
43
529
7
2
Order By: Relevance
“…Another report involved the chronic treatment of 10-month-old 5XFAD mice with the CSF1R inhibitor PLX3397, an orally bioavailable agent that crosses the BBB and results in the actual elimination of around 80% of microglia [112]. At this age, these mice display extensive amyloid pathology and neuronal loss.…”
Section: Modulation Of Microglial and Astrocytic Response And Functionmentioning
confidence: 99%
“…Another report involved the chronic treatment of 10-month-old 5XFAD mice with the CSF1R inhibitor PLX3397, an orally bioavailable agent that crosses the BBB and results in the actual elimination of around 80% of microglia [112]. At this age, these mice display extensive amyloid pathology and neuronal loss.…”
Section: Modulation Of Microglial and Astrocytic Response And Functionmentioning
confidence: 99%
“…In neurodegenerative disease or following traumatic brain injury, microglia can assume long‐lasting changes in morphology, densities, gene expression, and cytokine/chemokine production. Studies have indicated that these signals, when persistent in the brain, can lead to further harm (Dheen, Kaur, & Ling, 2007; Rice et al, 2015; Spangenberg et al, 2016). …”
Section: Introductionmentioning
confidence: 99%
“…In addition, amyloid associated microglia have been shown to be primarily derived from peripheral monocytes and may aggravate AD-like phenotypes (23,60). In addition, recent studies indicated that infiltrating peripheral monocytes clustered around amyloid plaques, but do not effectively clear plaques (61) and eliminating microglia did not affect amyloid load (62). We speculate that these observations may explain our findings that caspase-4 enhance microglial homing to plaques, yet failed to promote degradation or clearance.…”
Section: Discussionmentioning
confidence: 59%